CINGCOWONG, THE RITUAL OF SUMMONING RAIN - Aghniya al mahmudah (Cinematology: Journal Anthology of Film and Television Studies, 2022)
Cingcowong is a ritual to summon rain from Luragung Landeuh Village, Kuningan, West Java. The ritual makes the doll as an intermediary asking for rain which later the doll will be possessed by a spirit while chanting a spell asking for rain, and a few moments later it will rain. Many responses were made by several parties related to the existence of this ritual because it was considered outside the boundaries of religious teachings, so that in the end the Cingcowong ritual began to lose its sacred value and changed its function into an art performance. Because of this negative response, many parties also want to preserve this cultural heritage so that it does not become extinct by innovating new arts adapted from the Cingcowong ritual. This study uses a qualitative method with a descriptive analysis approach, through interviews with selected informants, observations, documentation and literature studies all obtained. This study found that the Cingcowong ritual ceremony is still ongoing today and there is a shift in values other than the ceremonial ritual to become a tourist attraction. The implications of this research as the main data in making a documentary.